Effects of Covid-19 on Mental Health of Older Adults: Study based on perceptions and experiences of adults suffered from Covid-19 - Uzma Ashiq, Nargis Abbas, Ibad Ullah Sajid, Maham Shafiq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The objective of this conceptual study was to know the effects of COVID-19 on mental health of older adults. Study design: This qualitative study was conducted in October-December 2022 in District Sargodha. Twenty (20) older adults who have been suffered from COVID-19 were taken as respondents selected through snowball-purposive sampling technique. A semi-structured interview protocol was used to collect data through in-depth interviews from the respondents. Thematic analysis method of qualitative methodology of research was used to analyze the data to find the results. Results: The study found that older adults experienced severe mental health issues during COVID-19 period due to loneliness, isolation, anxiety and fear of disease and death. During the quarantine period and hospitalization, loneliness and social isolation affected the mental health of the older adults. Fear of disease & death and losing the loved ones negatively affected the older adults psychologically to great extent. However, respondents who were educated and well aware of causes and consequences of the disease; used this information and awareness as coping strategy and such respondents had less adverse affects on their mental health. Conclusion: COVID-19 virus affected the well-being of older people with regard to mental and emotional. Social isolation and loneliness have been observed as main factors affecting the mental condition of older adults during the pandemic. They experienced grave psychological issues due to loneliness and fear of disease & death during the quarantine/ hospitalization period. Keywords: COVID-19, Older adults, isolation, quarantine, fear, mental, health.